Geometric quantum discords of interacting qubits in thermal reservoir - Zhao Li (Nature Portfolio, 2017)
Abstract We examined decay dynamics of various geometric quantum discords (GQDs) for two interacting qubits described by the Heisenberg XY model and further coupled independently to their respective thermal reservoirs. Compared to the case of noninteracting qubits, our results showed that decay rates of the GQDs can be retarded apparently by properly choosing system parameters of the interaction term. In the long-time limit, the asymptotic values of the GQDs are enhanced evidently by tuning anisotropy of the model and strength of the transverse magnetic field. We further illuminated the relations between different GQDs on characterizing quantum correlations, and observed multiple sudden change behaviors of their dynamics.